2016
DOI: 10.1111/hdi.12430
|View full text |Cite
|
Sign up to set email alerts
|

Results of human factors testing in a novel Hemodialysis system designed for ease of patient use

Abstract: Introduction Home hemodialysis has not been widely adopted despite superior outcomes relative to conventional in-center hemodialysis. Patients receiving home hemodialysis experience high rates of technique failure owing to machine complexity, training burden, and the inability to master treatments independently. Methods We conducted human factors testing on 15 health care professionals (HCPs) and 15 patients upon release of the defined training program on the Tablo™ Hemodialysis System. Each participant comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 13 publications
(24 reference statements)
1
12
0
Order By: Relevance
“…14 There are a number of possible reasons for the limited uptake of home hemodialysis in the United States, including (1) gaps in nephrologist training and experience; (2) generally low levels of patient engagement and activation; (3) fear of self-cannulation; (4) lack of 1 or more trained dialysis partners or caretakers; and (5) technical challenges brought on by nonintuitive machine design. 18 Studies conducted in the self-care hemodialysis setting indicate that patients can independently, accurately, and rapidly manage treatments with Tablo including setup and resolution of any alarms that may occur. [15][16][17] The Tablo ® Hemodialysis system was designed to address several of the barriers to home hemodialysis through a consumer-centric design focused on increasing patient engagement with a system that is easy to learn and use ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 There are a number of possible reasons for the limited uptake of home hemodialysis in the United States, including (1) gaps in nephrologist training and experience; (2) generally low levels of patient engagement and activation; (3) fear of self-cannulation; (4) lack of 1 or more trained dialysis partners or caretakers; and (5) technical challenges brought on by nonintuitive machine design. 18 Studies conducted in the self-care hemodialysis setting indicate that patients can independently, accurately, and rapidly manage treatments with Tablo including setup and resolution of any alarms that may occur. [15][16][17] The Tablo ® Hemodialysis system was designed to address several of the barriers to home hemodialysis through a consumer-centric design focused on increasing patient engagement with a system that is easy to learn and use ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Human factors studies have shown that the Tablo system is easy to learn. 18 Studies conducted in the self-care hemodialysis setting indicate that patients can independently, accurately, and rapidly manage treatments with Tablo including setup and resolution of any alarms that may occur. 19 The objective of the current investigational device exemption (IDE) trial was to evaluate the safety and efficacy of Tablo when used in-center managed by trained health professionals and in-home by trained patients or a care partner.…”
Section: Introductionmentioning
confidence: 99%
“…Similar methodologies have been employed for other HHD systems to assess the clinical safety and performance of the systems within controlled clinical environments prior to roll‐out in home settings. For example, HFT was conducted for the recently developed Tablo hemodialysis system with Healthcare Professionals and patients …”
Section: Discussionmentioning
confidence: 99%
“…For example, HFT was conducted for the recently developed Tablo hemodialysis system with Healthcare Professionals and patients. 27 This HFT study does have certain limitations; although the home is the principle target environment for use of SC +, usability testing is difficult to execute in the home. However, our simulated home environment was deemed an adequate representation, particularly because it included similar distractions that would be found in a home, such as televisions, noise from patients and staff, and variation in lighting conditions (i.e., bright sunlight hitting the screen, as well as low ambient lighting conditions).…”
Section: Discussionmentioning
confidence: 99%
“…Although some have been adapted for home use, more recently manufacturers have begun focusing on machines specifically developed for home therapy use and patient operation [11,12]. Such an approach has necessitated an improved understanding of industrial design, human factors and ergonomics to ensure that the burden of undertaking treatment in the home is reduced for the patient and their care partner [13,14].…”
Section: Plos Onementioning
confidence: 99%